Contribution to the Discussion about the Czech Republic's Accession to the European Union (Czech Journal of International Relations, 2002)
International Workshop on the Czech Republic's Accession to the European Union. 1st ed. Prague: Institute of Integration of the Czech Republic into the European and World Economy and University of Economics, 2001, 138 s., ISBN 80-245-0191-0.